Research trend of bacterial leaf blight on rice in the millennium era: a bibliometric and scientometric approach for capture future insight - Somantri, Renny Utami; Syahri, Syahri (Universitas Lampung, 2024)
In the 21st century, population growth affects food demand, especially rice. Xanthomonas oryzae pv. oryzae causes bacterial leaf blight (BLB) disease, the worldwide rice production problem. As pathogen pathotypes vary, research into disease control advances rapidly. Thus, these trends must be mapped to inform future studies. This study aims to examine previous research using bibliometric and scientometric methods to inform future research. Scopus publication data was analyzed utilizing VOSviewer and CiteSpace. Research progress, popular research, productive countries, productive researchers, essential keywords, and global collaboration were explored. Analysis of recent research data predicts future trends. The findings indicate that 21st-century BLB research is advancing at an astounding rate and significantly surpasses that of previous periods, with 596 articles (91.69%) published during this era. Agricultural and Biological Sciences is the leading focus due to its substantial emphasis on genetics-related issues. A statistical analysis of the most prolific countries over the past two decades reveals that the United States, China, and India produce the highest number of articles. China and India are the two largest rice producers, respectively. Nevertheless, the most productive authors reveal that Szurek B (a French scientist) ranks first with a staggering twenty articles. Three main research clusters were found that consisted of “antibacterial agents vs. bacterial disease,” “plant resistance and immunity mechanisms,” and “pathogen virulence and pathogenicity genes.” The study about resistance genes against disease became the most cited article. We concluded that there are several future insights, including “further investigation into the alternative antibacterial agent and their formulation,” “spatial distribution, severity, and prevalence of BLB in multiple conditions,” “the microbial community on plant leaves,” and “additional research to comprehend the mechanism of the microbial community in the rice rhizosphere.” In addition, research on the stability of plant resistance genes to anticipate changes in pathogen pathotypes will be an alternative topic.